The role of SOX family in cancer stem cell maintenance: With a focus on SOX2 - Pouremamali, Farhad; Vahedian, Vahid [UNESP]; Hassani, Nasrin; Mirzaei, Sepideh; Pouremamali, Amir; Kazemzadeh, Hamid; Faridvand, Yousef; Jafari-gharabaghlou, Davoud; Nouri, Mohammad; Maroufi, Nazila Fathi (Elsevier, 2022)
The role of cancer stem cells (CSCs) in cancer incidence, drug resistance, and relapse after chemotherapy has been discussed and it has been confirmed that CSCs are extremely important and so, are suitable for therapeutic targeting. Sox families play an important role in carcinogenesis and dis-regulation of SOXs molecules has been observed in different types of cancers. The members of this family have been shown to play an important role in the maintenance of CSCs. In this article, we have tried to evaluate the role of different family members in CSCs maintenance, review various studies in this field and provide a perspective view on this issue. Also, due to the important role and many studies in the field of SOX2 molecule in CSCs, we try to have more focus on this molecule and examine the potential of these molecules for therapeutic targeting.
Keywords: Cancer Stem Cells; Drug resistance; Maintenance; SOX family; SOX2